Expanding the knowledge about Aflatunia ulmifolia (Franch.) Vassilcz. (Rosaceae), a rare forest species of Central Asia - Kirillov, Vitaliy; Stikhareva, Tamara; Ivashchenko, Anna; Sitpayeva, Gulnara; Kuliyev, Arstanbek; Serafimovich, Mariya; Daulenova, Meirzhan; Zholdasbayev, Mussa (Botany letters)
Aflatunia ulmifolia (Franch.) Vassilcz. is a rare, poorly studied species from the Rosaceae Juss family. Its natural distribution range is limited to Central Asia (Western Tien Shan, Pamir-Alay, Dzhungarskiy and Kirghiz Alatau). Information on the current state of natural plant communities with the participation of A. ulmifolia, the introduction potential, and the methods of conservation of the species is limited. The aim of our study was to improve information about A. ulmifolia, by verifying its current distribution range, both in natural habitats and in places where it is introduced, and analyze the major ecological, morphological and biological characteristics of the species. We produced the most up-to-date species distribution map showing both natural and introduced populations of A. ulmifolia. For the first time, we provide a comprehensive list of tree and shrub species co-occurring with A. ulmifolia in Tajikistan, Kyrgyzstan, and Kazakhstan. We present detailed information on the successful introduction of A. ulmifolia in nine European and Asian countries. Although the species is not of immediate conservation concern, it might become vulnerable to extinction if its distribution range continues to shrink because of anthropogenic impact and natural disturbances. We argue for the development of effective conservation strategies for A. ulmifolia in nature and for the creation of stable introduction populations of this species in botanical gardens and arboretums.